The effect of Science-Technology-Society teaching on students' attitudes toward science and certain aspects of creativity - Lee, Mee-Kyeong; Erdogan, Ibrahim (Routledge Journals, Taylor & Francis Ltd, 2007)
The purpose of the study was to examine the effectiveness of Science-Technology-Society approaches on student attitudes toward science and creativity. Seven Korean Physics teachers (two middle school and five high school) who participated in a 4-week intensive summer Iowa Chautauqua Professional Development Program at the University of Iowa and their 591 students in 14-class section were participants in this study. Students who were taught with Science Technology - Society approaches showed significant improvement in the development not only of more positive attitudes toward science, but also of their creativity skills.
Keywords: High-School; Achievement; Sts; Questions